2007
DOI: 10.1002/chin.200750059
|View full text |Cite
|
Sign up to set email alerts
|

New N‐Heterocyclic Carbene Ligand and Its Application in Asymmetric Nickel‐Catalyzed Aldehyde/Alkyne Reductive Couplings.

Abstract: Alcohols P 0110New N-Heterocyclic Carbene Ligand and Its Application in Asymmetric Nickel--Catalyzed Aldehyde/Alkyne Reductive Couplings. -Various functional groups are tolerated in the procedure. Generally, the trialkylsilyl group is regioselectively installed at the newly formed hydroxyl group. In the case of substrate (IId), the regioselectivity in the coupling with (VI) is reversed with ligand (Ib). The methodology is also applied to the asymmetric macrocyclization of ynal (IX). In this case, the regiosele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…A mixture of three diastereomeric catalysts (17,33:50) was obtained as shown in the related literature. 20,27,31 On the other hand, just <2% 2a−c e.e. change and nearly exactly the same borylation yield were noted by replacing the ortho-H on L1 with D, suggesting that the H/D just behaved the same and ortho-CH oxidative addition is unlikely involved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A mixture of three diastereomeric catalysts (17,33:50) was obtained as shown in the related literature. 20,27,31 On the other hand, just <2% 2a−c e.e. change and nearly exactly the same borylation yield were noted by replacing the ortho-H on L1 with D, suggesting that the H/D just behaved the same and ortho-CH oxidative addition is unlikely involved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…48 This preference is contrary to the common expectation based on the steric model at first sight, especially when compared to those employed C 2 -symmetric designs 2 and in chiral NHC-Ni cases with the same Y-ring. 20,27 Yet, it can be explained by other competing steric repulsions in the syn-/anti-catalysts under different tilted angles (Scheme 2). Indeed, the tilted N-aryl on the syn-catalyst adopts a configuration that can accommodate the apparently more bulky o-Cy and the core's Ph sitting on the same side (torsion angle ∼100°).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Montgomery et al reported that a Ni-catalyzed triethylsilane asymmetric reductive coupling of an aldehyde and an alkyne produced the triethylsilylated allylic alcohol with good regioselectivity, yield and ee values (Scheme 143). 136 The aryl substituent of NHC ligand L81 was critical for high enantioselectivity. Regioselectivity was influenced by the two alkyne substituents; an alkyne with an aryl and alkyl group was optimal, while examples with two small alkyl groups exhibited poor regioselectivity.…”
Section: Asymmetric Reductive Coupling Of Aldehydes and Ketones With ...mentioning
confidence: 99%